A bibliography of sign languages : 2008-2017 - Aarssen, Anne; Genis, René; Veken, Eline van der (BRILL, 2018)
This concise bibliography on Sign Languages was compiled on the occasion of the 20th international Congress of Linguists in Cape Town, South Africa, in July 2018. The selection of titles is drawn from the Linguistic Bibliography and gives an overview of scholarship on Sign language over the past 10 years. The introduction is by Myriam Vermeerbergen (KU Leuven & Stellenbosch University) and Anna-Lena Nilsson (NTNU - Norwegian University of Science and Technology) gives an overview of the most recent developments in the field.